Bound sets and two-point boundary value problems for second order differential systems - Jean Mawhin; Katarzyna Szymańska-Dębowska (Mathematica Bohemica, 2019)
The solvability of second order differential systems with the classical separated or periodic boundary conditions is considered. The proofs use special classes of curvature bound sets or bound sets together with the simplest version of the Leray-Schauder continuation theorem. The special cases where the bound set is a ball, a parallelotope or a bounded convex set are considered.